UNDERSTANDING STUDENTS’ RETENTION TO USE DIGITAL FOOD BANKS: AN EXTENDED UTAUT2 - Che Aznan, Nur Alia Atirah; Yasin, Nurul Hafizah Mohd; Che Abdul Rahim, Norsyamlina (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME’S (AIJBES), 2026)
The growing use of digital platforms in charitable food aid has led to the emergence of digital food banks, yet existing research shows limitations in technology acceptance models when explaining their adoption. Prior studies have largely focused on single user groups, particularly recipients, thereby overlooking the dual-user nature of digital food banks that involve both donors and recipients within a shared value-exchange system. This conceptual paper aims to address this gap by proposing an extended Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) framework to examine intention and use behaviour toward digital food bank platforms. Drawing on UTAUT, the paper highlights the roles of performance expectancy, effort expectancy, social influence, and facilitating conditions in shaping users’ behavioural intention and use behaviour. By integrating insights from specific domain framing, this study offers a more comprehensive understanding of technology adoption within community-based digital food banks. The proposed framework offers a theoretical foundation for future empirical studies and provides practical implications for policymakers and platform developers seeking to enhance participation, sustainability, and effectiveness of digital food bank initiatives.